In tes ti nal Pa ra si tism and Associated Sanitary-Hygienic Factors In Individuals of Rural Localities in Sucre State - L. Mora; M. Segura; I. Martínez; L. Figuera; S. Salazar; I. Fermín; B. González (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
The present study was carried out to determination the frequency intestinal parasitisms and its associated sanitary hygienic factors in the rural localities Orinoco La Peña, Quebrada Seca and San Juan River. A total of 562 feces samples were analyzed, by different coproparasitological methods: microscopic evaluation in 0.85% physiological saline solution and lugol, Ritchie, as well as the Zielh-Neelsen stainin. The highest frequencies of intestinal parasites was found in Orinoco La Peña and Quebrada Seca. Blastocystis hominis (44.9%, 21.82%, 33.74%) and Giardia duodenalis (20.41%, 9.7%, 19.02%) were most commonly observed. The frequency of helminths varied depending on the studied community, but observing more frequently Ascaris lumbricoides, Trichuris trichiura and Ancylostomids. When evaluating the sanitary and hygienic factors associated to parasitosis we found a relationship between feces excretion (X2: 23,85***; p<0,001), water treatment (X2: 34,00***; p<0,001), and hygienic habits with presence of protozoans in individuals from Quebrada Seca, as well as with the presence of garbage disposal services (X2: 5,17*; p<0,05 ), presence of helminths were associated with the water source (X2: 13,97***; p<0,001) and hygienic habits. In Orinoco La Peña and San Juan River water treatment (X2: 11,56*; p<0,05; and X2: 21,5 **; p<0,01 ) was associate to presence of protozoans. The high frequencies of parasites indicates that the sanitary conditions and hygienic habits were favorable factors for the infection and infestation of parasites, combined to the environmental factors and deficiency health of services characteristic of these rural communities. Sanitary intervention from governmental authorities is necessary to improve environmental reparation and preventive sanitary education.